A South African perspective on some critical issues regarding the OECD model tax convention on income and on capital, with special emphasis on its application to trusts - Du Plessis, I. (Stellenbosch : Stellenbosch University, 2015)
Thesis (LLD)--Stellenbosch University, 2014.